Medicinal plants used by the indigenous peoples of Banskhali Upazila of Chattogram district, Bangladesh - Sultanul Amir, M. Julfiqar; Sadia, Halima Tujj; Bussmann, Rainer W.; Ashrafuzzaman, M. (Ethnobotany Research and Applications, 2025)
Background: People use many plants from the very beginning of the civilization for medicinal purpose. The aim of this study was to document the use of medicinal plants in Banskhali upazila of Chattogram district, Bangladesh. The ethnobotanical results contain qualitative and quantitative information on medicinal plant diversity as well as local name, plant part used, disease category, application method and plant habit. This information is documented for the first time in this area. Methods: A survey was conducted to collect data using group discussions and oral face-to-face interviews by using a semi-structured questionnaire covering personal information, information about plants and the importance of conserving valuable plant species among 220 residents of this area. Results were analyzed using quantitative indices of fidelity level (FL), frequency citation (FC), use value (UV), use report (UR) etc. Results: This survey documented 71 plant species from 38 families, detailing their botanical names, local names, plant parts used and traditional applications. Asteraceae, Fabaceae, and Lamiaceae are most represented families each with 5 species, followed by Apiaceae, Apocynaceae, Combretaceae, Lauraceae, Malvaceae, Rutaceae, and Zingiberaceae (each with 3 species). Leaves were the most commonly used part, followed by fruits, bark, stems and flowers, and whole plants, along with other parts like bulbs, cloves, rhizomes, seeds, roots, and husks as crude form, extracts, decoctions, infusions or pastes. The study documented 11 ailment categories, like gastrointestinal disorders, skin diseases, menstrual disorders, arthritis, diabetes etc. Conclusions: The study highlighted that elderly and illiterate individual preferred medicinal plants due to their affordability, distrust in modern medicine and aversion to surgery. However, these plants are threatened by exotic species, lack of awareness and overexploitation. The study advocates for immediate policy interventions to ensure their conservation. Keywords: Bangladesh, Banshkhali, Chattogram, Indigenous people, Medicinal plants